Influence of parenting styles on addiction to internet in peruvian secondary students - Matalinares C., María (2013)
Present study aimed to establish influence of parenting styles on addiction to Internet. 2370 teenage students from third to fifth grades of secondary school were evaluated. They belonged to 14 representative cities of coast, highlands and forest Peruvian regions and aged 13 to 18 years. Parenting Styles Questionnaire (Parker et al. 1997), adapted to our reality for the present study, and Addiction to Internet Test (Young, 1998), also adapted to our reality by Raymundo, Matalinares and Baca (2013, pending publication) were the instruments applied. Results showed that dysfunctional parenting styles (abuse and indifference) influenced on addiction to Internet. Greater incidence of teenage students addicted to Internet was observed in the coast while greater perception of dysfunctional parenting styles was observed in highlands. Dysfunctional parenting styles (indifference, abuse, overprotection) on one-parent family homes were also found.